Applications, benefits, and challenges of genome edited crops - Evanega, Sarah; Brown, Zachary; Bubeck, Dave; Falck-Zepeda, José B.; Chou, Fan-Li; Graham, Nat; Karavolias, Nicholas; Tripathi, L.; Yerka, Melinda (Council for Agricultural Science and Technology, 2024)
The paper discusses the advancements and potential of genome editing in agriculture, highlighting how genome editing tools, first described over a decade ago, are now being applied across various crops and trait combinations, promising benefits for producers and consumers.